UNIQUE AUTOMATED HANDLING SYSTEM IN ALTENWERDER INTERMODAL TERMINAL - Stopka, Ondrej; Sulgan, Marian (Doprava a spoje, 2012)
The paper deals with the general characteristics of Altenwerder intermodal terminal (Also known: CTA - Container Terminal Altenwerder) and then describes its unique handling system with intermodal transport units. Reloading of containers in Altenwerder intermodal terminal takes place in four phases which are carried out in various service areas. There is very important the utilisation of Automated Guided Vehicles, Automatic Stacking Cranes and Semi-automated Gantry Cranes in this terminal.